2010
DOI: 10.1002/marc.200900712
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Elegance of Chemistry in Designing Dendrimers

Abstract: Highly functional and monodisperse macromolecules with tailored architecture constitute the key to designing efficient and smart nanomaterials. Dendrimers offer real potential to achieve this goal, and one of the earlier challenges faced by this novel class of polymers has been addressed by the evolution of synthetic methodologies. This review provides an evaluation of the role played by chemistry in taking these macromolecules of academic relevance to practical industrial and biological applications, in a rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 201 publications
0
69
0
Order By: Relevance
“…Interestingly, the four characteristic bands of the pyrenyl part found in the region 290−390 nm are much stronger in the encapsulated systems than in the spectra of the free pyrenyl derivatives. For example, the molar Chem3D simulations, 27 used to gain some structural information, show the dendritic arm extending from the metallaprism with the pyrenyl moiety being encapsulated inside the cavity (Figure 5) 6 were evaluated against human ovarian A2780 (cisplatin sensitive) and A2780cisR (acquired resistance to cisplatin) cancer cell lines. Their cytotoxicities, in comparison to cisplatin, are presented in Table 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the four characteristic bands of the pyrenyl part found in the region 290−390 nm are much stronger in the encapsulated systems than in the spectra of the free pyrenyl derivatives. For example, the molar Chem3D simulations, 27 used to gain some structural information, show the dendritic arm extending from the metallaprism with the pyrenyl moiety being encapsulated inside the cavity (Figure 5) 6 were evaluated against human ovarian A2780 (cisplatin sensitive) and A2780cisR (acquired resistance to cisplatin) cancer cell lines. Their cytotoxicities, in comparison to cisplatin, are presented in Table 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The aromatic part of the pyrenyl-functionalized dendrimers may be encapsulated into the hydrophobic cavity of the hexanuclear a r e n e r u t h e n i u m m e t a l l a c a g e s [ R u 6 ( p -c y m ene) 6 (OO∩OO) 3 6+ ; tpt =2,4,6-tri(pyridin-4-yl)-1,3,5-triazine). 17 In contrast to the previously reported pyrenyl-dendrimers in metallaprism [1] 6+ , 16 the biological activity of both the dendrimers and of the host−guest systems has been evaluated.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two commonly used synthetic strategies for dendrimers include divergent and the convergent methods (Buhleier et al, 1978;Tomalia et al, 1984;Newkome et al, 1985;Tomalia et al, 1985;Hawker, Frechet, 1990;Hourani, Kakkar, 2010). The divergent method uses bottom-up approach where the synthesis of dendrimer is carried out beginning at the central core and moves towards the surface (Figure 1).…”
Section: Synthesis Of Dendrimersmentioning
confidence: 99%
“…Recently, Tomalia and his group suggested that dendrimers themselves can exhibit anti-inflammatory properties mainly through inhibiting COX-2 activity (Chauhan et al, 2009). Kakkar's group recently showed that dendrimers synthesized using alkyne-azide "click" chemistry act as antiinflammatory agents (Castonguay et al, 2011;Hourani, Kakkar et al, 2010;Sharma et al, 2011a,b). Dendrimers with terminated acetylene (A) (DG0-A, DG1-A and DG2-A) and hydroxyl groups (OH) (DG1-OH) (Hourani et al, 2010) have shown to inhibit the LPS-induced nitric oxide (NO) and COX-2 (involved in prostaglandin (PGE2) synthesis in N9 microglia cells (resident immune cells of central nervous system).…”
Section: Arachidonic Acidmentioning
confidence: 99%